Penerapan Pendidikan Karakter Sebagai Solusi Dalam Pertumbuhan Dan Perkembangan Peserta Didik Yang Baik - Mahardika, I Ketut; Mukarromah, Nadia; Septyaningtyas, Martha; Purnamasari, Dwika Citra Ayu (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to see the application of character education as a solution in the development and growth of students. This article is a review article of several selected articles. The result of this article is that character education in children means helping prepare a generation of people with character. Because they are candidates for the nation's next generation who are expected to be able to lead the nation and create a civilized country, uphold the noble values ​​of the nation with good morals and manners and become a generation with high knowledge and adorn themselves with faith and piety. Students who have implemented character education will learn to be religious, honest, diligent, disciplined, caring and have a full sense of responsibility.